Increasing IPS Learning Outcomes Through Discovery Learning Model For VII Class Students Of SMP Negeri 9 Kendari - I Wayan Lasdiartika (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
This study aims to improve the learning outcomes of social studies subjects in class VII SMPN 9 Kendari through the application of the discovery learning model. This research was conducted in the odd semester of the 2019/2020 academic year, at SMPN 9 Kendari for class VII students, totaling 32 students. The indicators observed in this study were student learning outcomes and activities. This research was carried out in 2 (two) cycles, including: a) planning; b) implementation of actions; c) observation and evaluation, d) reflection. The data obtained in this study were analyzed using descriptive statistics. The results showed that the social studies learning outcomes of seventh grade students of SMP Negeri 9 Kendari increased significantly, it was seen from the observation scores. This increase was shown in the activity achieved between the first cycle 56.25% in the poor assessment category, and 87.5% in the second cycle in the 87.5% category. good rating. Learning by applying the Exploratory Discovery method has a positive impact on student learning outcomes, this increase is shown in the first cycle based on the average grade of 71.41 with a completeness percentage of 37.5%, increasing in the second cycle with an average grade of 85.91 with a completeness percentage of 87.5%.